PROSPECTS OF THE USE AND ANALYSIS OF BIOMASS TYPES OF THE POLTAVA REGION AS SOURCES OF ELECTRICAL ENERGY - Basova, Yulia; Levchenko, Yulia; Suprovych, Oleksandr (Sworld-Us Conference proceedings, 2023)
The fight against energy and environmental problems continues continuously and at an ever-increasing pace. The development of renewable energy sources in the world is connected with limited energy resources. Most of all in Ukraine, the use of biomass ene